2021
DOI: 10.1002/alz.12248
|View full text |Cite
|
Sign up to set email alerts
|

Associations between plasma neurofilament light, in vivo brain pathology, and cognition in non‐demented individuals with autosomal‐dominant Alzheimer's disease

Abstract: Background Neurofilament light (NfL) is a promising biomarker of early neurodegeneration in Alzheimer's disease (AD). We examined whether plasma NfL was associated with in vivo amyloid beta and tau, and cognitive performance in non‐demented presenilin‐1 (PSEN1) E280A mutation carriers. Methods Twenty‐five mutation carriers and 19 non‐carriers (age range: 28 to 49 years) were included in this study. Participants underwent 11C Pittsburgh compound B (PiB)‐PET (positron emission tomography), flortaucipir–PET, bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Our group showed that Presenilin 1 ( PSEN1 ) E280A mutation carriers, who are destined to develop early‐onset dementia, have elevated levels of plasma P‐tau217 4 and NfL, 13 approximately 20 years before symptom onset. We also showed that, in carriers, higher levels of plasma P‐tau217 and NfL were associated with worse memory performance 4,14,15 …”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our group showed that Presenilin 1 ( PSEN1 ) E280A mutation carriers, who are destined to develop early‐onset dementia, have elevated levels of plasma P‐tau217 4 and NfL, 13 approximately 20 years before symptom onset. We also showed that, in carriers, higher levels of plasma P‐tau217 and NfL were associated with worse memory performance 4,14,15 …”
Section: Introductionmentioning
confidence: 65%
“…We also showed that, in carriers, higher levels of plasma P-tau217 and NfL were associated with worse memory performance. 4,14,15 Several studies investigating sex differences in AD have shown that females may have greater neurodegeneration 16,17 and tau pathology, as measured by cerebrospinal fluid, 18 PET imaging, 19,20 and postmortem neuropathology. 21,22 Moreover, studies show that females may exhibit a cognitive resilience to early accumulation of ADrelated pathology and neurodegeneration at the initial stages of the disease [23][24][25] ; however, as the disease progresses, females exhibit faster cognitive decline 16,26 and progression to dementia 22,[27][28][29] than males.…”
Section: Introductionmentioning
confidence: 99%
“…NEFL is also an established biomarker of early neuronal injury and axonal degeneration that has been shown to be elevated in preclinical AD 53 . For example, pre-symptomatic PSEN1 mutation carriers had higher plasma NfL levels than non-carriers and higher NfL levels were associated with greater regional tau burden and worse cognition, but not amyloid β load 54 . INA showed an increase in transcript but both an increase and decrease in protein, for different peptides, whereas NEFL shows It is plausible that the presence of tau seed in these cells causes gene expression changes through interference in neurofilament formation.…”
Section: Discussionmentioning
confidence: 97%
“…NFs have been detected in both cerebrospinal fluid (CSF) and peripheral blood (SP) (49). In a cohort of 1,070 PSEN1 E280A mutation carriers and 1,074 noncarriers with baseline assessments and 242 mutation carriers and 262 noncarriers with longitudinal (6±3 years) measures, ranging in age from 8 to 75 years, plasma NFL levels increased with age in both groups and began to differentiate carriers from noncarriers at age 22 (22 years before the estimated median age of mild cognitive impairment) (50,51). This biomarker is released in to the CSF and SP as the inflammatory process and gliosis progress in the white matter, and has been correlated with cortical and hippocampal atrophy, widening of the ventricles, memory impairment and mild cognitive impairment (52,53).…”
Section: Alzheimer's Diseasementioning
confidence: 99%